Prevalence of aortic aneurysms and dissections in patients with systemic vessel aneurysms and dissections; matched case-control study using a national sample cohort - Song, Jihye; Lim, Yong Cheol; Kim, Do Jung (Frontiers in Cardiovascular Medicine, 2023)
Objective: Aneurysms in systemic arteries are rare, and little is known about their relationship with aortic aneurysms. In tThis study, we aimed to evaluate the prevalence of aortic aneurysms and dissections (AAD) in patients with other systemic vessel aneurysms and dissections (OVAD) and identify their potential risk factors.This cross-sectional study used a nationwide representative cohort sample from the Korea National Health Insurance Service-National Sample Cohort database. We defined OVAD as systemic vessel aneurysms and dissections excluding intracranial and aortic dissections and aneurysms. With a total of 690 OVAD patients and 2,760 non-OVAD matched controls, we investigated the prevalence of AAD in patients with OVAD and potential risk factors for their concurrence using the χ 2 test and logistic regression.The prevalence of AAD in patients with OVAD was 10.6% (73/690) and 0.3% (9/2760) in patients with non-OVAD. The adjusted odds ratio (OR) for having concurrent AAD with OVAD was 37.56 (95% CI: 18.29-77.12, p <0.001) after stratificationed by sex, age, income, region of residence and after adjustmented forby hypertension, diabetes mellitus, dyslipidemia, and extent of disability. The adjusted ORs of AAD were significantly higher in patients with females (adjusted OR =47.63[, 95% CI: 10.72-211.55]), and individuals aged ≥ 60 years (adjusted OR =28.18,[ 95% CI: 13.42-59.17]), as well as those withoutnon-hypertension (adjusted OR =95.44,[ 95% CI: 18.21-500.23]), non-diabetes mellitus (adjusted OR =46.39, [95% CI: 18.85-114.17]), non-without dyslipidemia (adjusted OR =60.99,[ 95% CI: 20.83-178.56], p <0.001 for all). The prevalence of AAD significantly differed by according to specific AAD in patients with OVAD sites of OVAD showed significant differences in carotid artery, upper extremity artery, iliac artery, lower extremity artery, and splanchnic artery (p <0.001 for all).The prevalence of AAD in patients with OVAD was 37.56 times higher than that in the matched population. We may approach aneurysms as systemic diseases and further investigations of pathophysiology would help to clarify their relationshipsthe relationships between AAD and OVAD.